Inquiry in television cooking shows. (June 2015) - Matwick, Kelsi; Matwick, Keri
This article raises the important question as to why cooking, a seemingly mundane practice, performs social and cultural functions that go much beyond cooking, cooking instructions, and food preparation, and specifically how it functions in a media context. By integrating theories about inquiry, discourse analysis, gender, and sociolinguistics, the article makes an important contribution to the growing literature on contemporary discourse in the media. The research was conducted on popular television cooking channels, the Food Network and the Cooking Channel, and involved close analyses of a sample of instructional cooking shows. The article is an exploration of social and communicative dynamics inherent in cooking, especially from the public discourse of contemporary cooking shows.